Application of social competence of religious college lecturers in building a harmonious campus life - Sukri, Urbanus (ARKA INSTITUTE, 2025)
Lecturers' social competence is essential in fostering a harmonious academic environment, particularly in religious universities where moral, spiritual, and cultural values intersect. This study investigates how social competence measured through communication, empathy, conflict management, and collaboration affects campus harmony. Employing a mixed-methods approach, data were collected through a survey of 150 lecturers and students and in-depth interviews with 15 lecturers. Multiple linear regression analysis revealed that social competence significantly predicts campus harmony. Communication and empathy emerged as the most influential dimensions, followed by collaboration and conflict management. Classical assumption tests confirmed the validity of the model. Thematic analysis of qualitative data reinforced these findings, highlighting that informal dialogue, emotional sensitivity, and cooperative engagement are central to building inclusive and respectful campus communities. The integration of both data types through triangulation validated the multidimensional impact of social competence. This study concludes that social competence must be institutionalized through structured training and policy reforms in religious universities to improve educational climate and interpersonal relations. Findings contribute to the discourse on relational pedagogy, emphasizing that social competence is not peripheral but central to holistic education.